Entomopathogenic fungi: Are polisporic isolates more pathogenic than monosporic strains? - Aguilera Sammaritano, Juan Alberto (2017)
Currently only monosporic strains from several entomopathogenic fungi have been selected and used for mass production and bioinsecticide manufacturing worldwide. The main reasons for the use of single spore instead of multispore strains are the attenuated virulence and the contaminants of the same species. In this study, different polisporic isolates and their monosporic combinations were tested against Tenebrio molitor (Linnaeus) larvae as an insect model. Isolates were obtained from arid soils. Four Metarhizium sp. (Metschn.) multisporic isolates (CEP413, CEP589, CEP590 and CEP591) were selected for bioassays. Trials were performed to evaluate mortality on three treatments, Full Polisporic (FP), Partial Polisporic (PP) and Pure Monosporic (PM). Cumulative mortality was measured at day 4 post infection. Sporulation percentage was assessed at day 6 post infection. The highest mortality was found at FP treatment (94%), the lowest mortality at day 4 was found at PM-CEP413 (32%). At day 6 the sporulation percentage was higher on FP (94%) and it was different from the rest of the treatments. To elucidate different polisporic and monosporic combinations to improve their effectiveness, may help to expand the use of bioinsecticides based on entomopathogenic fungi.